2003
DOI: 10.1002/jbm.b.10033
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship between tensile bond strength and dimensions of bonded area

Abstract: It is a known fact that there is a relationship between magnitude of bonded area and laboratory tensile test results. This relationship has been described for a range of areas between 1 and 10 mm 2 , in extracted, nonperfused teeth. The aim of this study is to test this relationship in perfused teeth, with bonded areas ranging from 0.7 to 110.9 mm 2 . Dentin of 92 sound third human molars was exposed and perfused, and three groups of bonded areas (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
10
1
4
Order By: Relevance
“…In this study, the μTBS was used to evaluate bond strength. This test is more desirable than the shear bond test, which mostly results in cohesive fractures far from the resin/ceramic interface and errors in bond strength evaluation . Sano et al demonstrated that tensile bond strength has an inverse relationship with the cross‐sectional area of the bonded surface, and recommended using the microtensile bond test …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the μTBS was used to evaluate bond strength. This test is more desirable than the shear bond test, which mostly results in cohesive fractures far from the resin/ceramic interface and errors in bond strength evaluation . Sano et al demonstrated that tensile bond strength has an inverse relationship with the cross‐sectional area of the bonded surface, and recommended using the microtensile bond test …”
Section: Discussionmentioning
confidence: 99%
“…This test is more desirable than the shear bond test, which mostly results in cohesive fractures far from the resin/ceramic interface and errors in bond strength evaluation. 29,30 Sano et al demonstrated that tensile bond strength has an inverse relationship with the cross-sectional area of the bonded surface, and recommended using the microtensile bond test. 20 Comparing the μTBS of studied groups, the LiSaE group showed the highest bond strength, although there was no significant difference between the LiSaE and LiSa groups (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The bond strength typically decreases with increasing bonded surface area. 10,11 An alternative fracture mechanics approach for determining the adhesion at bimaterial interfaces has been described by Charalambides et al 12 The method has already been applied in dentistry to evaluate interfacial fracture toughness in terms of strain energy release rate (G) of various metal-ceramic bonding systems. From these studies, it has been suggested that the bimaterial bond test geometry combined with interfacial fracture toughness measurement is an appropriate alternative method for studying the bonding characteristics of a porcelain-fused-to-metal systems.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing results of bond strength investigations for both shear and tensile mode of loading based on the surface area for the same adhesive systems, it was found that microtensile bond values were 2-5 times higher than that recorded by macrotensile test. For shear testing, the microshear bond values were 1.2-3 higher than those revealed by the macroshear test [11,12] . In addition, studies revealed higher average macroshear bond values than macrotensile ones [13,14] .…”
Section: Type Of Testmentioning
confidence: 64%